Chirality and life a short introduction to the early phases of chemical evolution - Flügel, Rolf M.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book presents the fascinating formation of the first simple bioorganic molecules and describes the hidden aspects of chiral compounds, which raise questions on the molecular beginnings of life. The occurrences of extraterrestrial, non-standard amino acids in meteorites are dealt with in detail, as well as their subsequent transfer to proteinogenic amino acids. The concept of asymmetric organo-catalysis for the synthesis of carbohydrates and ribonucleosides are considered. The notion of a single amino acid that functions as an enzyme is developed. Attempts to simulate ancient world scenarios are critically reviewed. There is a special focus on ribozymes and the resulting RNA world. Combinations of different world scenarios are discussed in view of an on-going evolution. The currently most plausible hypotheses and visions of ancient world scenarios that led to today?s DNA world are also provided. Included is a pre-cellular world of viruses that is presented for the first time.
Part I. Physico-chemical Principles -- 1. Introduction -- 2. Formation of Primordial Bioorganic Molecules -- 3. Hidden Aspects of Chirality -- 4. RNAs and Their Constituents -- 5. Proteins and Their Constituents -- 6. Membranes -- 7. Compounds Required for Life Part II. Scenarios of Ancient Worlds -- 8. The RNA World Involves RNA as a First Genetic System -- 9. Peptide and Protein World -- 10. Combinations of the RNA with the Peptide World -- 11. The Precellular World of Viruses -- 12. Combinations of Different Worlds -- 13. The Iron Sulfide World of Proto-Metabolism -- 14. The Genetic Code.
Electronic reproduction.
Keywords: Chirality; Molecular evolution; Electronic books